Capturing the dynamic profiles of products in Hailaer brown coal pyrolysis with reactive molecular simulations and experiments. (15th May 2020) - Zheng, Mo; Pan, Yang; Wang, Ze; Li, Xiaoxia; Guo, Li
Graphical abstract: Highlights: A combined strategy for capturing dynamic profiles of Hailaer coal prolyzates. ReaxFF MD simulations and experiments of SVUV-PIMS and Py-GC/MS were employed. Consistent identification of pyrolyzates obtained from simulations and experiments. Three generation pathways for phenol revealed by ReaxFF MD simulation. Approaches of simulations and experiments corroborate and complement each other. Abstract: This work aims at exploring the possible applications of the state-of-the-art methods in uncover the dynamic product profiles in coal pyrolysis. A combination of pyrolysis with the synchrotron vacuum ultraviolet photoionization mass spectrometry (Py-SVUV-PIMS), flash pyrolysis technique with gas chromatography-mass spectrometry (Py-GC/MS) and reactive molecular dynamic simulations (ReaxFF MD) was employed in capturing product distributions in Hailaer brown coal pyrolysis. The consistent identification of the representative pyrolyzates obtained from simulations and experiments suggest that mono-aromatic hydrocarbons and alkyl-phenols are major tar products. It is clearly observed that dimethyl-phenol is most likely the primary product for Hailaer coal pyrolysis after analyzing the spectrograms of Py-SVUV-PIMS and Py-GC/MS experiments. The three phenol generation pathways first reveal that the hydrogen atoms to stabilize phenoxyl radicals can come from surrounding structures, CHO2 intermediates and large fragments to help CO2 generation and condensation reactions. These results indicate ReaxFF MD with a reasonable coal model can provide rich clues for reactions involved with important pyrolyzates. The combined pyrolysis approaches can complement each other in capturing dynamic profiles for major products in different pyrolysis stages, including primary pyrolyzates of Py-GC/MS, primary and secondary pyrolyzates of Py-SVUV-PIMS, and the underlying reaction pathways of ReaxFF MD simulations.